2016
DOI: 10.3390/md14040063
|View full text |Cite
|
Sign up to set email alerts
|

The Bacterial (Vibrio alginolyticus) Production of Tetrodotoxin in the Ribbon Worm Lineus longissimus—Just a False Positive?

Abstract: We test previous claims that the bacteria Vibrio alginolyticus produces tetrodotoxin (TTX) when living in symbiosis with the nemertean Lineus longissimus by a setup with bacteria cultivation for TTX production. Toxicity experiments on the shore crab, Carcinus maenas, demonstrated the presence of a paralytic toxin, but evidence from LC-MS and electrophysiological measurements of voltage-gated sodium channel–dependent nerve conductance in male Wistar rat tissue showed conclusively that this effect did not origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…More recently, there have been reports of the presence of the TTX-producing bacteria Bacillus sp. 1839 in C. simula isolated from the Sea of Japan [ 55 ], fitting with the findings of other authors who have established that these species and other species of bacteria such as Vibrio alginolyticus may play an important role in either the production or accumulation of toxin within nemerteans [ 23 , 56 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Introductionsupporting
confidence: 85%
“…More recently, there have been reports of the presence of the TTX-producing bacteria Bacillus sp. 1839 in C. simula isolated from the Sea of Japan [ 55 ], fitting with the findings of other authors who have established that these species and other species of bacteria such as Vibrio alginolyticus may play an important role in either the production or accumulation of toxin within nemerteans [ 23 , 56 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Introductionsupporting
confidence: 85%
“…To deduce the biological function of α-nemertides we used an established model organism to study toxicity of nemertean mucus in vivo : the green crab Carcinus maenas 5,7 . This model has biological significance because crustaceans are both well-known preys and possible predators of nemerteans 13 .…”
Section: Resultsmentioning
confidence: 99%
“…L. longissimus first sparked our interest as a possible source of tetrodotoxin (TTX). However, TTX could never be identified, but the mucus still showed potent activity when injected into the branchial chamber of green crabs ( Carcinus maenas ) 7 . Instead, as shown in the current work, the activity is explained by the presence of a novel family of disulfide-rich peptide toxins.
Figure 1The nemertean Lineus longissimus and schematic of its phylogeny.
…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that although the genus Vibrio, widespread in marine ecosystems, was commonly reported as the main bacterial TTX-producer, its ability to produce the toxin was questioned. Strand et al [32] showed that using liquid chromatography-mass spectrometry (LC-MS) and bioassay for TTX detection in bacterial and nemertean samples might lead to false-positive results and should be supplemented with tandem mass spectrometry (MS/MS). The authors revealed a compound produced by Vibrio alginolyticus isolated from the ribbon worm Lineus longissimus.…”
Section: Discussionmentioning
confidence: 99%